2020
DOI: 10.21037/atm.2020.03.87
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high flow nasal cannula on peripheral muscle oxygenation and hemodynamic during paddling exercise in patients with chronic obstructive pulmonary disease: a randomized controlled trial

Abstract: Background: Exercise training for patients with chronic obstructive pulmonary disease (COPD) improves their endurance and oxygenation. Supplemental oxygen delivered by high flow nasal cannula (HFNC) reportedly improves the clinical outcomes during high-intensity exercise. However, the physical benefits of the provision of supplemental oxygen with HFNC for the improvement of exercise performance have not been fully investigated. This randomized trial aimed to evaluate the effect of HFNC on the hemodynamic statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…We found three ongoing studies. We excluded 35 reports and finally included 5 studies (Fang et al., 2020; Hsiao et al, 2018; Tung et al., 2020; Vitacca et al., 2019; Volpi et al., 2022) with 8 reports, as two studies had more than one associated publication. See the PRISMA flow diagram in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We found three ongoing studies. We excluded 35 reports and finally included 5 studies (Fang et al., 2020; Hsiao et al, 2018; Tung et al., 2020; Vitacca et al., 2019; Volpi et al., 2022) with 8 reports, as two studies had more than one associated publication. See the PRISMA flow diagram in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…All included studies were RCT. Three studies were conducted in Taiwan (Fang et al., 2020; Hsiao et al, 2018; Tung et al., 2020) and two in Italy (Vitacca et al., 2019; Volpi et al., 2022). The studies included 300 patients with COPD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another RCT of 32 moderate to severe stable COPD patients, Fang et al compared the effect of HFO to conventional nasal oxygen supplementation on peripheral muscle oxygenation and hemodynamics during paddling exercise. 25 The HFO arm achieved better hemodynamics than the nasal oxygen arm as demonstrated by a higher cardiac index (CI) which was the primary outcome. Another trial in Argentina (ClinicalTrials.gov ID NCT02973945), with an intended 60 COPD patients, comparing the use of HFO against 40% oxygen supplementation via Venturi mask during pulmonary rehabilitation is underway.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, previous studies have reported that patients with COPD who exercised with HFNC support exhibited an extended exercise time and greater peripheral oxygen extraction than those using traditional oxygen equipment [16,20], suggesting a potential decrease in COB associated with HFNC support. Conversely, a recent meta-analysis of this therapeutic tool in respiratory rehabilitation of patients with CCDs did not show a positive impact on lung mechanics, breathing patterns, and exercise capacity [21].…”
Section: Introductionmentioning
confidence: 96%